If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -12y + 5 = 2(y + -8) Reorder the terms: 10 + 5 + -12y = 2(y + -8) Combine like terms: 10 + 5 = 15 15 + -12y = 2(y + -8) Reorder the terms: 15 + -12y = 2(-8 + y) 15 + -12y = (-8 * 2 + y * 2) 15 + -12y = (-16 + 2y) Solving 15 + -12y = -16 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 15 + -12y + -2y = -16 + 2y + -2y Combine like terms: -12y + -2y = -14y 15 + -14y = -16 + 2y + -2y Combine like terms: 2y + -2y = 0 15 + -14y = -16 + 0 15 + -14y = -16 Add '-15' to each side of the equation. 15 + -15 + -14y = -16 + -15 Combine like terms: 15 + -15 = 0 0 + -14y = -16 + -15 -14y = -16 + -15 Combine like terms: -16 + -15 = -31 -14y = -31 Divide each side by '-14'. y = 2.214285714 Simplifying y = 2.214285714
| -733=w+-425 | | 2x^2+9=109 | | 4n-8=-40 | | 10t+5t+t-15t=12 | | 5(x)=2x-10 | | x^2-2x+y^2-6y=-6 | | Log(6x-8)=0 | | 0(x)=2x-10 | | 2x/7-3=2 | | -9r(r+1)+6(1-3r)= | | -4=40/x*20 | | -2(x)=2x-10 | | 2(4+x)=2x+3 | | 0.5r=-15 | | 3-j=-j+3 | | 6q=84 | | x+y+2z=0 | | -34r-8=36 | | 8c-6c-c=11 | | 2k-12=4k | | 5x-8x=5x-8x | | 7x+12=8x | | -7(b+9)-2(10b-5)= | | 3x^2=-20 | | 3(6c+1)-18=16c+3 | | h(t)=-16t+150t+70 | | 4x=20 | | 16x-9-9=3x+18 | | 16c-11c-c+3c-4c=9 | | S-1/8=15/8 | | 4x(-7+7x)= | | h(t)=-16+150t+70 |